Overlooked diversity in African Solanum (Solanaceae): new and endangered Solanum agnewiorum from Kenya - Vorontsova, M. S.; Kirika, P.; Muthoka, P. (Phytotaxa, 2014)
Despite the almost universal occurrence of Solanum in Kenya, there continues to be a significant gap in floristic knowledge of this important genus. We describe Solanum agnewiorum from montane forest in the central highlands. We assess the IUCN conservation status of this species as Endangered.